The Effect of Active Learning Integrated with Everyone Is A Teacher Here Strategy Based on Questioning and Answering on The Critical Thinking Skills and Biology Learning Retention of Class XI Senior High School Students In The Industrial Agriculture Area - Suciningsih, Kurnia; Siswati, Bea Hana; Savira, Nadyatul Ilma Indah (Universitas Muhammadiyah Surakarta, 2023)
This study aimed to improve student’s critical thinking skill and student retention in learning biology through active learning strategy innovation Everyone Is A Teacher Here (ETH) based on Questioning and Answering (Q&A). Moreover, the type of research used is a quasi-experimental research using a pre-test, post-test, and re-test research pattern. In addition, the research was conducted at SMAN 3 Jember in the even semester of the 2022/2023 academic year. The XI MIPA 2 class was selected as the experimental class and XI MIPA 4 as the control class. Based on the results of this study, the ETH strategy based on Q&A has a significant effect on students' critical thinking skills and retention in biology class XI. This is evidenced by the results of the significance of the Anakova test using SPSS, critical thinking skills have a significance of 0.000 (p<0.05) and student retention has a significance of 0.000 (p<0.05). The innovative learning strategy used in this study can be applied in class because it can increase student focus and motivation, especially in biology.